Characterizing and comparing the spawning habitats of anchovy (Engraulis capensis) and sardine (Sardinops sagax) in the Southern Benguela upwelling ecosystem - Twatwa, Nandipha M (Department of Biological Sciences, 2014)
Bibliography: leaves 85- 97.